Role of Redox Status in Development of Glioblastoma - Salazar-Ramiro, Aleli; Ramírez-Ortega, Daniela; Pérez de la Cruz, Verónica; Hérnandez-Pedro, Norma Y.; González-Esquivel, Dinora Fabiola; Sotelo, Julio; Pineda, Benjamín (Frontiers in Immunology, 2016)
Glioblastoma (GBM) is a highly aggressive neoplasia, prognosis remains dismal and current therapy is mostly palliative. There are no known risk factors associated with gliomagenesis; however, it is well established that chronic inflammation in brain tissue induces oxidative stress in astrocytes and microglia. High quantities of reactive species of oxygen into the cells can react with several macromolecules, including chromosomal and mitochondrial DNA, leading to damage and malfunction of DNA repair enzymes. These changes bring genetic instability and abnormal metabolic processes favoring oxidative environment and increase rate of cell proliferation. In GBM, a high metabolic rate and increased basal levels of ROS play an important role as chemical mediators in the regulation of signal transduction, protecting malignant cells from apoptosis, thus creating an immunosuppressive environment. New redox therapeutics could reduce oxidative stress preventing cellular damage and high mutation rate accompanied by chromosomal instability, reducing the immunosuppressive environment. In addition, therapies directed to modulate redox rate reduce resistance and moderate the high rate of cell proliferation, favoring apoptosis of tumoral cells. This review describes the redox status in GBM and how this imbalance could promote gliomagenesis through genomic and mitochondrial DNA damage, inducing the pro-oxidant and pro-inflammatory environment involved in tumor cell proliferation, resistance and immune scape. In addition, are described some therapeutic agents that modulate redox status and might be advantageous in therapy against GBM.